Bahasa Inggris - Ayuninggar, Lintang; Pramest, Diah; Damayanti, Rosita Mei; Martin, Endang; Rosdaliva, Mehilda (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2023)
Micro, small and medium enterprises in Indonesia run and managed mostly in traditional and conventional administration due to the limited digital literation and organizational management knowledge of the MSMEs. However, some of these MSMEs are scaling up by implementing management procedure and digital system. They carry out human resource practice into their operation along with digital system into their routine. The development is driven mainly by the new environment brought by the COVID-19 pandemic which force business entities to be ready for digital operation. This study examines the effect of digital readiness in moderating the relationship of human resource management practice and MSME’s performance. We surveyed 357 MSMEs in various fields, including culinary, clothing, crafts, and services through questionnaire to collect the data. As predicted, digital readiness moderates the relationship between human resource management practice and MSME’s organizational performance. However, the moderation effect is not as expected. Data suggests digital readiness negatively moderates the relationship of human resource management practice and MSME’s organizational performance.